Mitochondrial homeostasis: a potential target for delaying renal aging - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Pharmacology, 2023)
Mitochondria, as the energy factory in the cell, participate in many life activities in the cell, and the kidney is a high metabolic organ, which contains abundant mitochondria. Renal aging is a degenerative process, with the accumulation of harmful processes. With the further study, more and more attention has been paid to the role of abnormal mitochondrial homeostasis in renal aging. However, the role of mitochondrial homeostasis in renal aging has not been reviewed in detail. Here, we summarize the current biochemical markers associated with aging, and also review the changes in renal structure and function during aging. Moreover, we also review in detail the role of mitochondrial homeostasis abnormalities, including mitochondrial function, mitophagy and mitochondria-mediated oxidative stress and inflammation, in renal aging. Finally, we describe some of the current anti-aging compounds that target mitochondria and point out that maintaining mitochondrial homeostasis is a potential anti-renal aging strategy.